Bridging the Gender Awareness-Participation Gap: A Quasi-Experimental Comparison of Psychoeducation and Group Counseling Among Young Adults - Sigit Sanyata; Salma Salsabila Hasna; Rizqi Lestari (WISE Pendidikan Indonesia, 2026)
Persistent social norms can sustain unequal gender roles even when individuals endorse equality in principle. This quasi-experimental pretest-posttest study compared structured psychoeducation with group counseling for strengthening gender equality orientation among young adults in Bantul Regency, Indonesia. Purposive sampling recruited 61 participants aged 20-30 years (psychoeducation, n = 31; group counseling, n = 30). Equivalent forms of the Gender Equality Scale assessed equality, access, participation, and harmony before and after the interventions. ANCOVA controlled baseline scores. The adjusted group effect was not statistically significant, F(1, 58) = 0.026, p = 0.873, partial eta squared = 0.0004; the full model was also nonsignificant, F(2, 58) = 1.762, p = 0.181. Descriptively, both conditions showed higher total posttest scores, but changes were uneven across dimensions, with participation remaining comparatively resistant. The study does not establish formal equivalence between interventions; rather, it indicates that a structured psychoeducational format can be considered a feasible awareness-building option alongside group counseling. Its principal contribution is the identification of participation as the priority target for subsequent behavior-oriented and gender-transformative intervention components.